Clinical significance of micronutrient supplements in patients with coronavirus disease 2019: A comprehensive systematic review and meta-analysis. (April 2022) - Beran, Azizullah; Mhanna, Mohammed; Srour, Omar; Ayesh, Hazem; Stewart, Jamie M.; Hjouj, Majdal; Khokher, Waleed; Mhanna, Asmaa S.; Ghazaleh, Dana; Khader, Yasmin; Sayeh, Wasef; Assaly, Ragheb
Summary: Background and aims: Micronutrient supplements such as vitamin D, vitamin C, and zinc have been used in managing viral illnesses. However, the clinical significance of these individual micronutrients in patients with Coronavirus disease 2019 (COVID-19) remains unclear. We conducted this meta-analysis to provide a quantitative assessment of the clinical significance of these individual micronutrients in COVID-19. Methods: We performed a comprehensive literature search using MEDLINE, Embase, and Cochrane databases through December 5th, 2021. All individual micronutrients reported by ≥ 3 studies and compared with standard-of-care (SOC) were included. The primary outcome was mortality. The secondary outcomes were intubation rate and length of hospital stay (LOS). Pooled risk ratios (RR) and mean difference (MD) with corresponding 95% confidence intervals (CI) were calculated using the random-effects model. Results: We identified 26 studies (10 randomized controlled trials and 16 observational studies) involving 5633 COVID-19 patients that compared three individual micronutrient supplements (vitamin C, vitamin D, and zinc) with SOC. Nine studies evaluated vitamin C in 1488 patients (605 in vitamin C and 883 in SOC). Vitamin C supplementation had no significant effect on mortality (RR 1.00, 95% CI 0.62–1.62, P = 1.00), intubation rate (RR 1.77, 95% CI 0.56–5.56, P = 0.33), or LOS (MD 0.64; 95% CI -1.70, 2.99; P = 0.59). Fourteen studies assessed the impact of vitamin D on mortality among 3497 patients (927 in vitamin D and 2570 in SOC). Vitamin D did not reduce mortality (RR 0.75, 95% CI 0.49–1.17, P = 0.21) but reduced intubation rate (RR 0.55, 95% CI 0.32–0.97, P = 0.04) and LOS (MD -1.26; 95% CI -2.27, −0.25; P = 0.01). Subgroup analysis showed that vitamin D supplementation was not associated with a mortality benefit in patients receiving vitamin D pre or post COVID-19 diagnosis. Five studies, including 738 patients, compared zinc intake with SOC (447 in zinc and 291 in SOC). Zinc supplementation was not associated with a significant reduction of mortality (RR 0.79, 95% CI 0.60–1.03, P = 0.08). Conclusions: Individual micronutrient supplementations, including vitamin C, vitamin D, and zinc, were not associated with a mortality benefit in COVID-19. Vitamin D may be associated with lower intubation rate and shorter LOS, but vitamin C did not reduce intubation rate or LOS. Further research is needed to validate our findings.